On New Properties of Differential Transform via Difference Equations - Al-Ahmad, S.; Mamat, M.; AlAhmad, R.; M. Sulaiman, I.; Liza Ghazali, Puspa; Afendee Mohamed, Mohamad (International Journal of Engineering and Technology, 2018)
The area of differential transform has been enjoying vivid growth recently, with a lot of emphasis on linear and nonlinear ordinary differential/difference equations. In this paper, we construct and prove new properties of differential transform; particularly, in the case of certain quotients of functions. We further presented interesting relations between the differential transform, the difference operator, and incomplete gamma functions. Numerical examples with encouraging results have been presented to illustrate the efficiency of the method.Â Â
Keywords: differential transform; differential equations; polynomial approximation.